Cultural and Religious Symbols in the Tradition of Pilgrimage to the Grave of Sheikh Burhanuddin - Ahmad Taufik Hidayat; Andri Rosadi; Sudarman Sudarman; Itra Antony (Universitas Darussalam Gontor, 2022)
This article examines the phenomenon of the pilgrimage of followers of the Syattariyah Order in Minangkabau to the tomb of Sheikh Burhanuddin. The focus of this article is on the forms of cultural and religious simbols that exist in the pilgrimage tradition to this tomb and how they are interpreted. The main data of this research are from field data, such as: interviews, observations, and historical objects around the tomb. An interviews data sources involve about 80 respondents. The focus of the study is the pilgrim's motives, simbols and meanings that accompany this tradition. The results of this study prove that the cultural simbols in this tradition are representations of the community's mindset, related to the socio-economic background that influences differences in the process of meaning and the practice of pilgrimages. The identified meanings of pilgrimage are: letting go of intentions, healing, expressing gratitude, charity, matchmaking, developing or perpetuating business, continuity of practice, respect for teachers and obtaining safety and peace.